Parkinson disease: identifying different players sharing a common principle - Farooqi, Ammad Ahmad; Arshad, Sadia; Fayyaz, Sundas; Abbas, Sana; Bhatti, Shahzad (Research in Biotechnology, 2011)
Parkinson disease is a multifactorial molecular disorder. Miscellaneous regulators have been characterized to date and their implication in disease progression is well documented. Compromised neuromuscular activity is a serious threat posed by malfunctioning of various regulators. The integrity and maintenance of neural architecture underpins neural activities. Despite the fact that various breakthroughs have been made, yet many proteins are unidentified while some unaddressed. Furthermore, miRNA pathway impairment results in subversion of core biological system and draws attention towards novel miRNA-based therapeutic strategies. Thus proteins and mitrons work in collaboration with various cellular organelles to ensure normal dynamics of neural circuitry. In this review we will emphasize the derailed activities of proteins at molecular level that might help in getting a step closer to personalized medicine.